All Days 2008
DOI: 10.2118/117327-ms
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Oil Recovery from Heavy Oil Waterfloods

Abstract: A statistical study of 166 western Canadian waterfloods recovering heavy and medium gravity oils revealed new findings about best operating practices for heavy oil waterflooding. In classical light oil waterflooding, operators are advised to start waterflooding early and maintain the voidage replacement ratio (VRR) at 1. The study, however, produced surprising results for 2 parameters − among the 120 reservoir and operating parameters investigated − that ran counter to the recommended practices of classical li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, the adverse mobility ratio between heavy oil and water greatly hinders the sweep efficiency of water flooding . In the process of water flooding, water fingers through the less mobile heavy oil, establishes high-velocity preferential flow paths, and bypasses a significant portion of the reservoir. , Therefore, the oil recoveries of heavy-oil water-flooding projects are generally low, and most of them even less than 20% of the OOIP . In the past decades, a lot of research has been performed to decrease the adverse mobility ratio of heavy oil and water and to constrain the viscous fingering.…”
Section: Introductionmentioning
confidence: 99%
“…However, the adverse mobility ratio between heavy oil and water greatly hinders the sweep efficiency of water flooding . In the process of water flooding, water fingers through the less mobile heavy oil, establishes high-velocity preferential flow paths, and bypasses a significant portion of the reservoir. , Therefore, the oil recoveries of heavy-oil water-flooding projects are generally low, and most of them even less than 20% of the OOIP . In the past decades, a lot of research has been performed to decrease the adverse mobility ratio of heavy oil and water and to constrain the viscous fingering.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the interlayer contradictions become prominent and the oilfield development is seriously affected. Many cases on the developmental laws of waterflooding performance via commingling production in multilayer reservoirs have been recorded in different oilfields in the U.S. [1][2][3], China [4][5][6][7][8][9][10][11], Canada [12,13] and Australia [14].…”
Section: Introductionmentioning
confidence: 99%
“…In other work, analysis of production data from numerous Canadian waterfloods shows a correlation between a reduced voidage replacement ratio (VRR) and increased oil recovery (Brice and Renouf 2008). VRR measures the ratio of injected to produced fluids at reservoir conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The examiners of the Canadian waterfloods concluded that performing primary depletion until recovery of a certain fraction of oil followed by a waterflood is optimal for heavy-oil reservoirs (Brice and Renouf 2008). They also concluded periods of reduced VRR are beneficial.…”
Section: Introductionmentioning
confidence: 99%